The Construction of Meaning and Position of Mental Disorder Character in Three Romance Films - Dite Nursyamsi Mahmutami (Universitas Islam Negeri Sunan Gunung Djati, 2020)
This research discusses the representation and discourse which focused on the elements of characterization and narration which is presented by mental disorder character in Silver Linings Playbook (2012), Touched with Fire (2015), and The Other Half (2016). In this research, mental illness is not analyzed as a medical narration but also is one of signifying practices. The approaches of media representation analysis from Simon Cross (2014) and Harper (2008) are used to determine the representation of life experiences and disassemble the emerging discourses. The result indicates that when mental illness is represented in the romantic film, the stereotype about abnormality, rejection, and exclusion still becomes the main structure of the narrative. The romance story that wraps it up still refers to the stereotype. Therefore, those three films can be concluded as a part of dominant statements on abnormality discourse against mental disorder sufferers. In this case, mental disorder sufferers are subjected as a subject that must change. It is because only one choice for mental disorder sufferers to be accepted in society, that is recovery.Keywords: Mental Disorder Character, Discourse, Representation, Film